ТИББИЁТ ХОДИМЛАРИДА КАСБИЙ ДЕОНТОЛОГИЯСИНИ ШАКЛЛАНТИРИШНИНГ ИЖТИМОИЙ-ПСИХОЛОГИК ХУСУСИЯТЛАРИ - Собирова, Д.А. (SCIENCE and SOCIETY, 2023)
This article highlights the scientific and theoretical foundations of the social deontologiya of health workers and the role and importance of the factors influencing it.
Keywords: social competence; social-psychological competence; identification; reflection; altruism